'Seeing with one's own eyes' and speaking to the mind: a history of the Wilson cloud chamber in the teaching of physics. Issue 2 (June 2021) - Bertozzi, Eugenio
Abstract: In 1911 the Wilson cloud chamber opened new possibilities for physics pedagogy. The instrument, which visualized particles' tracks as trails of condensed vapour, was adopted by physicists to pursue frontier research on the Compton effect, the positron and the transmutation of atomic nuclei. But as the present paper will show, Wilson's instrument did not just open up new research opportunities, but the possibility of developing a different kind of teaching. Equipped with a powerful visualization tool, some physicists–teachers employed Wilson's instrument to introduce their students to a wide range of phenomena and concepts, ranging from the behaviour of clouds to Einstein's photon, the wave–particle duality and the understanding of the nucleus. This paper uses the notes, books and prototypes of these pioneering physicists–teachers to compose a pedagogical history of the Wilson cloud chamber, documenting an episode of immense ingenuity, creativity and scientific imagination.